UNVEILING SYMBOLS OF EMPOWERMENT AND SELF-ENCOURAGEMENT IN AMANDA LOVELACE'S BREAK YOUR GLASS SLIPPERS - Dian Susanti, Erlina; Nuristama, Ramadhina Ulfa; Ikrima Sa’adah, Sufi (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2024)
Amanda Lovelace's Break Your Glass Slippers employs symbols such as the mirror, fairy godmother, sword, and lipstick to portray themes of strength and self-discovery. This study uses qualitative research methodologies and symbolic theory to investigate Lovelace's usage of these symbols. The mirror reflects self-perception, questioning society conventions and personal fears, whereas the fairy godmother deconstructs classic fairytale roles to provide empowerment and direction. Readers are encouraged to face obstacles confidently and assertively by the sword, which stands for strength and perseverance. Lipstick highlights the harmony between strength and sensitivity in the feminine experience, embodying femininity and agency. Lovelace's poetry promotes women's emancipation and the acceptance of unique stories via these symbols. This research attempts to improve readers' comprehension of Lovelace's writing and the ideas she presents by dissecting her use of imagery and figurative language. Through her poems, Lovelace offers people a method to face and overcome challenges in their own lives by creating a literary place for introspection and resiliency. The research emphasises how Lovelace's precise symbolism encourages readers to interact with themes of perseverance, self-discovery, and empowerment.